Antilipase and antioxidant activity of Orthosiphon stamineus methanolic extract - Alias, Norsyuhada; Leow, Adam Thean Chor; Mohamad Ali, Mohd. Shukuri; Salleh, Abu Bakar; Ahmad Tajudin, Asilah; Raja Abd. Rahman, Raja Noor Zaliha (Kulliyyah (Faculty) of Medicine, International Islamic University Malaysia, 2016)
Antilipase from natural resources are a potential tool for the treatment of obesity while antioxidant-rich plants are essential in combating degenerative diseases. The aim of this study is to determine the antilipase and antioxidant activity of Orthosiphon stamineus methanolic extract. The inhibitory activity against pancreatic lipase was determined by measuring the hydrolysis of p-nitrophenyl butyrate to p-nitrophenol at 405 nm. Antioxidant activity of O. stamineus extract was measured by 2, 2, diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity assay. The O. stamineus crude extract exhibited strong lipase inhibitory activity with an IC50 value of 34.7 µg/ml. The inhibition mode study disclosed that O. stamineus could act as uncompetitive inhibitor. O. stamineus showed high antioxidant activity with an EC50 value of 26.3 µg/ml. The results suggest that O. stamineus has shown potential as a source of natural antilipase and antioxidant.